Learning Gurindam Dua Belas Based on Role Playing with Audio Visualt to Strenghten Social Sensitivity Value of Students - Zaitun, Zaitun (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Gurindam Dua Belas is a local wisdom of the Riau Community which is full of character values, let alone taught to students through a targeted learning model. This study aimed to describe the strengthening of student's character through learning Gurindam Dua Belas based on Role Playing with Audio Visual. The research method carried out with Research and Development by Borg and Gall by looking at one of the character values, namey social sensitivity. Researchers conducted pre-test and post-test to find out whether Guridnam Dua Belas learning based on Role Playing with Audio Visual can improve care value in students. The sample in this study were students of the Maritime University of Raja Ali Haji Tanjungpinang from several faculties with a total sample of 174 people. The result is an increase in social sensitivity value in students after implementing the model